Quality housing for all: An overview on regulatory and administrative framework in Malaysia - Sufian, Azlinor (2007)
The housing industry in Malaysia is regarded as one of the major industries contributing to the economic and social development of the country. The housing industry in Malaysia is regulated by stringent rules and regulations in the form of; the Housing Development (Control and Licensing) Act, 1966 (“HDA”), the Street, Drainage and Building Act 1976 (“SDBA”) and the Town and Country Planning Act 1974. On the other hand as far as construction of houses under the category of low-cost is concerned, it is subjected to the standard guidelines i.e Construction Industry Standard (“CIS 1”) and Construction Industry Standard 2 (”CIS 2”). The imposition of regulations, guidelines and standards is to ensure that all categories of houses, inclusive of houses for the lower income group will be constructed according to the acceptable standard. However despite the enforcement of these regulatory measures yet, there are many problems faced by house buyers in Malaysia. One of the most common problems is sub-standard construction of houses. There is a standard form of contract of sale and purchase agreement (“SPA”) stipulated under the Housing Development (Control and Licensing) Regulations 1989 (“HD Regulations 1989”), yet as far as the problem of sub-standard construction of houses is concerned, Malaysian house buyers are not well protected. There are a few authorities in Malaysia such as the local authorities, the Ministry of Housing and Local Government (“MHLG”) and the Construction Industry Development Board (“CIDB”) which are expected to carry out the task of ensuring that houses constructed by developers are free from defects. In general there is no benchmark in Malaysia to measure the standard of quality of houses constructed by developers. It is the aim of this paper to look into some legal provisions (and its loopholes) related to duties of the three most important institutions related to the building of quality houses namely the local authorities, the MHLG and the CIDB in ensuring that houses constructed by developers will meet the quality that house buyers expect. It is hoped that all quarters involved in the Malaysian construction industry be they professionals or semi professional as well as policy makers will take into account the practices in other jurisdictions as references for the construction of quality houses.